Emerging role and function of Hippo-YAP/TAZ signaling pathway in musculoskeletal disorders - Juanjuan Han; Jiale Zhang; Xiaoyi Zhang; Wenxin Luo; Lifei Liu; Yuqing Zhu; Qingfeng Liu; Xin-an Zhang (Stem Cell Research & Therapy)
Abstract Hippo pathway is an evolutionarily conservative key pathway that regulates organ size and tissue regeneration by regulating cell proliferation, differentiation and apoptosis. Yes-associated protein 1 (YAP)/ WW domain-containing transcription regulator 1 (TAZ) serves as a pivotal transcription factor within the Hippo signaling pathway, which undergoes negative regulation by the Hippo pathway. The expression of YAP/TAZ affects various biological processes, including differentiation of osteoblasts (OB) and osteoclasts (OC), cartilage homeostasis, skeletal muscle development, regeneration and quality maintenance. At the same time, the dysregulation of the Hippo pathway can concurrently contribute to the development of various musculoskeletal disorders, including bone tumors, osteoporosis (OP), osteoarthritis (OA), intervertebral disc degeneration (IDD), muscular dystrophy, and rhabdomyosarcoma (RMS). Therefore, targeting the Hippo pathway has emerged as a promising therapeutic strategy for the treatment of musculoskeletal disorders. The focus of this review is to elucidate the mechanisms by which the Hippo pathway maintains homeostasis in bone, cartilage, and skeletal muscle, while also providing a comprehensive summary of the pivotal role played by core components of this pathway in musculoskeletal diseases. The efficacy and feasibility of Hippo pathway-related drugs for targeted therapy of musculoskeletal diseases are also discussed in our study. These endeavors offer novel insights into the application of Hippo signaling in musculoskeletal disorders, providing effective therapeutic targets and potential drug candidates for treating such conditions.